2011
DOI: 10.1055/s-0029-1245960
|View full text |Cite
|
Sign up to set email alerts
|

Chronisches Lidödem assoziiert mit Rosazea (Morbus Morbihan): Differenzialdiagnostische Schwierigkeiten und Therapieoptionen

Abstract: Morbus Morbihan can be diagnosed only after excluding other conditions leading to chronic lid swelling. In our series, good results were achieved with intralesional injection of triamcinolone. Surgery also led to relevant improvements for a long period (13 months), with some adjuvant therapy. The treatment of chronic eyelid oedema associated with rosacea remains a challenge for the ophthalmologist and the oculoplastic surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…6,10 In cases resistant to mainstay therapies, novel therapies including omalizumab, complex decongestive therapy (CDT), CO 2 blepharoplasty, and surgical eyelid debulking may be used, and have shown some potential for symptomatic improvement. [12][13][14] However among available cases, disease recurrence was noted within 6 months after treatment with CO 2 blepharoplasty and eyelid debulking regimens. 12,15 In two cases of isotretinoin-resistant disease, CDT was documented as providing improvement and later led to symptomatic resolution in one of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…6,10 In cases resistant to mainstay therapies, novel therapies including omalizumab, complex decongestive therapy (CDT), CO 2 blepharoplasty, and surgical eyelid debulking may be used, and have shown some potential for symptomatic improvement. [12][13][14] However among available cases, disease recurrence was noted within 6 months after treatment with CO 2 blepharoplasty and eyelid debulking regimens. 12,15 In two cases of isotretinoin-resistant disease, CDT was documented as providing improvement and later led to symptomatic resolution in one of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of Morbihan disease, some authors have reported the efficacy of nonsurgical treatment for facial lymphoedema, such as manual lymphatic drainage or compression bandaging 12,13 . Debulking blepharoplasty has often been performed for severe cases, but recurrent swelling is common in the literature 1,4 …”
Section: Discussionmentioning
confidence: 99%
“…9,11 In the treatment of Morbihan disease, some authors have reported the efficacy of nonsurgical treatment for facial lymphoedema, such as manual lymphatic drainage or compression bandaging. 12,13 FIGURE 2. Photograph of LVA.…”
Section: Procedures Simply Debulk Enlarged Tissue Of Lymphoedema To R...mentioning
confidence: 99%